2013
DOI: 10.3109/10408363.2013.847897
|View full text |Cite
|
Sign up to set email alerts
|

ApoB versus non-HDL-cholesterol: Diagnosis and cardiovascular risk management

Abstract: The most recent guidelines released by the EAS/ESC and the Canadian Cardiovascular Society (CCS) retain low-density lipoprotein cholesterol (LDL-C) as the primary measure of the atherogenic risk of the apolipoprotein B (apoB) lipoproteins and the primary target of LDL-C lowering therapy. Both organizations endorse non-high-density lipoprotein cholesterol (non-HDL-C) and apoB as "alternate/secondary" targets, but neither group offers evidence supporting the continued preference of LDL-C as the primary target ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Low HDL-C levels in patients with coronary artery disease are associated with a high risk for cardiovascular events [ 27 ]. LDL-c and non-HDL-c are likely to be the predictors of cardiovascular risk and as targets for treatment [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low HDL-C levels in patients with coronary artery disease are associated with a high risk for cardiovascular events [ 27 ]. LDL-c and non-HDL-c are likely to be the predictors of cardiovascular risk and as targets for treatment [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the postprandial state, the level of ApoB48 particles in healthy individuals is very low (27). Many studies have suggested that ApoB is a more accurate marker of cardiovascular disease than LDL-C or non-HDL-C (28)(29)(30). A meta-analysis from 12 independent epidemiological studies including 233,455 participants reported that the relative risk ratios of ischaemic cardiovascular events were highest for apoB (31).…”
Section: Discussionmentioning
confidence: 99%
“…Pragmatically, calculated LDL-C and non-HDL-C are acceptable to monitor apheresis. Values of these different lipid measurements should occupy the same centile in normal population distributions in order to be equivalent [49]. Interconversion of LDL-C and non-HDL-C is problematic because the conversion factor increases with lower LDL-C and increasing triglyceride concentrations, reflecting the lower proportion of LDL-C in non-HDL-C [50].…”
Section: Lipoprotein Targets In Hofhmentioning
confidence: 99%